DAMPAK PANDEMI COVID 19 TERHADAP KESEHATAN MENTAL ANAK DAN REMAJA : LITERATUR REVIEW - Sonartra, Era Neltia (LPPM STIKES MUHAMMADIYAH GOMBONG, 2021)
The newly identified human infection, caused by the coronavirus (SARS-CoV-2), is spreading rapidly around the world, posing a threat to population health and creating challenges for health systems. This disease of unknown and uncertain prognosis with the scarcity of medical equipment and personal protection has led to the adoption of measures that limit individual freedom. In addition to these factors, increased financial losses will contribute to widespread emotional distress and an increased risk of psychiatric disorders. The method used is an electronic search of articles collected from electronic databases such as Medline, Science Direct, and PubMed using relevant keywords, namely: The Covid 19 Pandemic, The Mental Health, Children and Adolescents. The articles selected are in accordance with the SPIDER criteria, published in 2019-2020. This search emphasized recent articles, consensus statements, guidelines, and prospective cohort studies, critically reviewed and selected by the authors. Research has also been carried out on the official website which is informative of the public domain and references contained in previously collected dataKeywords: The Covid 19 Pandemic, The Mental Health, Children and Adolescents